2002
DOI: 10.1034/j.1600-6143.2002.20717.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus‐Induced Glomerular Vasculopathy in Renal Allografts: A Report of Two Cases

Abstract: Cytomegalovirus (CMV) remains a major viral pathogen complicating renal transplantation. Tubulointerstitial nephritis is the commonly acknowledged and wellcharacterized pathologic feature of renal allograft CMV disease. There is controversy about whether there is a distinct entity as a CMV glomerulopathy in the absence of tubulointerstitial disease. We describe two patients with renal allograft dysfunction who displayed distinct features of CMV glomerular vasculopathy, in the absence of overt viral cytopathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
1
17
0
2
Order By: Relevance
“…Of note, histopathological grading (Table 4) might overestimate rejection especially in desensitized animals as CMV nephritis can show signs that are indistinguishable from rejection (eg, glomerulitis, peritubular capillaritis, tubulitis, etc). [42][43][44][45][46][47] It has been reported that CMV tends to affect kidneys in one of three patterns, (a) CMV infection within the glomerular endothelial cells, (b) CMV infection within the tubular epithelia cells, or (c) CMV in endothelial cells of a peritubular capillary. Interestingly, we exclusively observe peritubular capillary CMV in the desensitized animals ( Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, histopathological grading (Table 4) might overestimate rejection especially in desensitized animals as CMV nephritis can show signs that are indistinguishable from rejection (eg, glomerulitis, peritubular capillaritis, tubulitis, etc). [42][43][44][45][46][47] It has been reported that CMV tends to affect kidneys in one of three patterns, (a) CMV infection within the glomerular endothelial cells, (b) CMV infection within the tubular epithelia cells, or (c) CMV in endothelial cells of a peritubular capillary. Interestingly, we exclusively observe peritubular capillary CMV in the desensitized animals ( Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Tubulointerstitial nephritis caused by CMV is the more common manifestation in renal allograft . CMV glomerulopathy, which can occur with or without concomitant tubulointerstitial disease, has been reported . A case of CMV‐induced necrotizing and crescentic glomerulonephritis in renal transplant patient has been described .…”
Section: Discussionmentioning
confidence: 99%
“…HCMV infection of the kidney may also result in direct endothelial injury, with subsequent HCMV glomerulopathy [36,38]. A prompt decline in serum creatinine levels after institution of intravenous ganciclovir (without anti‐rejection therapy) has also been described in patients with HCMV glomerulopathy, but without tubulointerstitial changes [38]. In the study of Boyce et al.…”
Section: The Impact Of Hcmv Infection and Disease On Acute Rejection mentioning
confidence: 99%